PEMBELAJARAN YANG BERORIENTASI PADA PAKEM (Pembelajaran Aktif, Kreatif , Efektif, dan Menyenangkan) - Rus’an Rus’an; Syaryanto Syaryanto (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
The teaching and learning process greatly determines the improvement of the quality of education. Learning acquisition in the form of certain values and skills measured through learning processes and results. The past learning system is considered to be no longer able to sustain the overall educational goals. Therefore, efforts to innovate in the field of learning are always developed. The approach in learning that is considered relevant to answer the demands of the times is an active, creative, effective and fun approach or commonly abbreviated as PAKEM. That said, because the PAKEM approach can accommodate the demands for the development of all aspects of the child, both cognitive, affective and psychomotor.